Impact of climate change on cost and cost efficiency of solar irrigation in Sub-Saharan Africa - Xie, Hua; Ringler, Claudia (Earth and Space Science Open Archive, 2024)
Irrigation is considered a promising option for improving agricultural productivity in Sub-Saharan Africa. To support irrigation expansion in the region, solar-powered irrigation systems are increasingly being promoted due to limited grid connections, fuel supply constraints, and gradual declines in their costs. However, compared to fossil fuel-based irrigation systems, the performance of solar irrigation systems is more sensitive to climate changes. This paper evaluates the impact of climate change on the cost and cost efficiency of stand-alone solar irrigation systems across Sub-Saharan Africa under five CMIP6 SSP5-8.5 climate change scenarios. We find that climate change will increase the investment cost and erode the cost efficiency of solar irrigation systems relative to diesel irrigation in most countries and crop areas across the region. However, the decline in the cost performance of solar irrigation is expected to be moderate and might well be offset if the cost of solar panels continues to decrease.